Plan estratégico para la empresa “Pavi Pollo” de la ciudad de Loja para el periodo 2017-2021 - Riofrio Tituana, Sandra Valeria (2016)
This thesis denominated “Strategic Plan for the Company "Pavi Pollo" Loja City , for the period 2017 -2021" has the objective to establish a planning in terms of procedures and actions that will enable the company to improve the organizational structure and economic development can in that way establish competitive advantages and further stability, growth and permanence in the market. First of all an analysis was performed it was very helpful in terms of practice and development of the Strategic Plan, of theoretical support bibliographical, inductive, deductive, scientific, analytical and synthetic method and techniques were used as observation, the interview for the administrator ; 20 surveys for the personal who is working in the company, and 400 surveys for the customers in order to get information highly relevant to establish a diagnostic of the company and identify the weaknesses and strengths of the company. an external analysis was performed based on the factors such as economic, technological, political - legislative and social which were analyzed to identify opportunities or threats that may affect business activities. With the results of external analysis it proceeds to perform Matrix EFE. obtaining a weighted value of 2.52 which shows that the company is not taking advantage of opportunities and it doesn't avoid threats of the medium, in the same way after making internal analysis and determined the strengths and weaknesses EFI Matrix was made obtaining as weighted value of 2.62 shows that the strengths are a little stronger than the threats but slightly because there are issues that affect to the company. Once done the complete internal and external analysis of the environment, it proceed to elaborate the FODA matrix And then the develop of four types of strategies FA, FO ,DA,DO and designing MATRIX HIGH IMPACT to determine strategies that are essential base for strategic objectives: Determine the organizational structure of the company to assist the development and competitiveness of it, Improve knowledge and skills of all staff working as much as the administrative and operational level that will strengthen the market position, To motivate the staff working in the company "Pavi Pollo" inducing them to improve the level of job performance, Implement sales techniques that motivate the consumer to gain the service, Establish competitive advantages that ensure earn the preference of customers in order to stay on the market. Once determined each of the strategic objectives it proceeded to detail the parts of the plan such as objectives, strategy, tactics, policy, activities, schedule, and budget responsibility. The total cost of the objectives of the proposal is $ 15.283,03 moreover a timetable which will set the order of performance of each activity was established. Finally it proceeded to make the necessary findings to the subject and several recommendations that can help improve the development of the company.